Flexibilidade e resistência torcional de instrumentos de niti e de aço inoxidável utilizados na exploração de canais radiculares - Rodrigo Keigo Lopes Nakagawa (2011)
The mechanical properties of endodontic instruments are affected by factors such as diameter, design, chemical composition and physical properties. The aim of this study was to evaluate the flexibility and torsional resistance of PathFile, ISO 10 RaCe and Scout RaCe NiTi rotary instruments intetend for the "glide path", in comparison with that of conventional stainless steel K-File instruments. The chemical composition of the instruments was analyzed by X-ray Energy Dispersive Spectroscopy (EDS), the phases were identified by X-ray Diffraction (XRD) and the transformation temperatures were determined by Differential Scanning Calorimetry (DSC). Longitudinal and cross sectional images of the instruments were used to measure their diameter and area at 3 mm from the tip (D3 and A3), the position where mechanical loads are concentrated during clinical use. The mechanical behavior was evaluated by bending and torsion tests, in accordance with specification ISO 3630-1. All instruments showed geometric features within the tolerance limits, but RaCe ISO 10/.02 and Scout RaCe 15 and 20 .02 taper instruments showed changes in cross-sectional design, triangular to square, possibly to increase their torsional resistance. NiTi instruments were significatively more flexible than the stainless steel ones, although their torsional resistance was lower. Clinically, PathFile, RaCe ISO 10 and Scout RaCe NiTi instruments represent a most compatible choice with the proposal of the "glide path". Although presenting less torsional resistance than the K-File instruments, the use of these NiTi instruments may maintain the original way of root canal better than the stainless steel instruments.